Effects of cross head speed on properties and energy absorption of sandwich AL/PU-PTFE foam composite - Rosaniza Md Isa (School of Materials Engineering, 2015)
The scope of this research is to analyse the surface Electromyography signals from five lower right dominant limb muscles during dynamic cycling at two different saddle heights. The signals recorded from seven healthy normal active male subjects, due to gender differences in muscle fatigue between male and female only male subjects selected. The tests done in a controlled room environment, using electric ergometer controlled by computer software. The recorded signals then analysed and the extracted features are subjected to a statistical analysis to compare the difference of each presented methods in terms of fatigue. Kinesiology software used to analyse the recorded video during cycling to measure the knee joint angle during the full cycle at each saddle height.